Eggplant Germination is Promoted by Hydrogen Peroxide and Temperature in an Independent but Overlapping Manner - Dufková, Hana; Berka, Miroslav; Luklová, Markéta; Rashotte, Aaron M; Brzobohatý, Břetislav; Černý, Martin (Molecules (Basel, Switzerland), 2019)
Hydrogen peroxide promotes seed germination, but the molecular mechanisms underlying this process are unclear. This study presents the results of eggplant (Solanum melongena) germination analyses conducted at two different temperatures and follows the effect of hydrogen peroxide treatment on seed germination and the seed proteome. Hydrogen peroxide was found to promote eggplant germination in a way not dissimilar to that of increased temperature stimuli. LC-MS profiling detected 729 protein families, 77 of which responded to a temperature increase or hydrogen peroxide treatment. These differentially abundant proteins were found to be involved in a number of processes, including protein and amino acid metabolism, carbohydrate metabolism, and the glyoxylate cycle. There was a very low overlap between hydrogen peroxide and temperature-responsive proteins, highlighting the differences behind the seemingly similar outcomes. Furthermore, the observed changes from the seed proteome indicate that hydrogen peroxide treatment diminished the seed endogenous hydrogen peroxide pool and that a part of manifested positive hydrogen peroxide effect might be related to altered sensitivity to abscisic acid.
Keywords: fyziologický stres; eggplant; Chromatography, Liquid; Temperature; proteomics; Carbohydrate Metabolism; teplota; hydrogen peroxide; regulace genové exprese u rostlin; metabolismus sacharidů; seed; Gene Expression Regulation, Plant; Stress, Physiological; Gene Expression Regulation, Developmental; Germination; chromatografie kapalinová; peroxid vodíku; rostlinné proteiny; Plant Proteins; vývojová regulace genové exprese; Solanum melongena; klíčení; hmotnostní spektrometrie; Hydrogen Peroxide; temperature; germination; Mass Spectrometry